Bioactive protein/peptides of flaxseed: A review. (October 2019) - Wu, Shufen; Wang, Xiaochan; Qi, Wei; Guo, Qingbin
Abstract: Background: Flaxseed meal, the de-oiled by-product of flaxseed processing, has been extensively studied as a rich source of protein (with protein content up to 40%). Flaxseed protein (FP) and FP-derived peptides from flaxseed meal have documented physiological activity, e. g. angiotensin-converting enzyme (ACE) inhibition, antibacterial activity and anti-diabetic effect as well as antioxidant capacity. However, the mechanisms for their physiological activities and the structure & bioactivity relationships have not been summarised previously. In addition, commercial production of FP and its peptides is still not achievable due to challenges in production scale up and real-time quantification of bioactives. Scope and approach: Previous studies including isolation and structural features of FP as well as the production, biological activities and the structural & functional relationships of bioactive peptides/hydrolysates from FP are herein reviewed. This article would be helpful to promote the application of FP/bioactive peptides in both research and commercialization. Key findings and conclusions: As interactions between flaxseed gum (FG) and FP interfere with FP isolation, removal of FG before extraction is necessary. Therefore, combination strategies are required for FP production. Lab-scale peptide generation is both costly and time-consuming. To overcome this challenge, in-silico methods are suggested, including mathematical simulation of protein hydrolysis, bioprospecting for bioactive peptides, and molecular docking studies. Gastrointestinal analysis is recommended for studying practical applications of FP-derived peptides as bioactive nutrients. Highlights: Removal of flaxseed gum can improve the separation process of flaxseed protein. More information about the structure of flaxseed protein is needed. Specific flaxseed protein-derived bioactive peptides are desired.